TABLET FORMULATION OF ETHANOLIC EXTRACT FROM RED DRAGON FRUIT (Hylocereus costaricensis) PEEL USING CASSAVA STARCH AS THE DISINTEGRANT - Nurullah Asep Abdilah; Dwi Astuti; Usman Setiawan (Fakultas Farmasi Universitas Muslim Nusantara Al Washliyah, 2026)
Introduction: Red dragon fruit peel (Hylocereus costaricensis) contains antioxidant compounds that can be utilized as active substances in tablet preparations. Objective: The purpose of this study was to determine the effect of variations in the concentration of manihot amylum as a crushing agent on the physical properties of tablets of ethanol extract of H. costaricensis fruit peel by wet granulation. Methods: Ethanol extract of H. costaricensis fruit peel was made by maceration method then phytochemical screening and antioxidant activity test using DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Tablets of ethanol extract of H. costaricensis fruit peel were made in 3 formulas based on manihot amylum concentration, namely 10 (F1), 15 (F2) and 20% (F3). Results: The results showed that the IC50 value of the ethanol extract of H. costaricensis fruit peel was 252.31 ppm. Variations in the concentration of manihot amylum as a crushing agent affect the physical properties of tablets, namely the optimum formula F2 (15%) with a hardness test result of 5 Kg, a friability test of 0.95% and a disintegration time test of 4.25 seconds; F3 (20%) with a hardness test result of 5.1 Kg, a friability test of 0.58% and a destruction time test of 7.10 seconds and F1 (10%) with a hardness test of 5.5 Kg, a friability test of 0.42% and a destruction time test of 8.30 seconds. Conclusions: Ethanol extract of red dragon fruit peel (Hylocereus costaricensis) can be formulated into tablet preparations with manihot amylum as a crushing agent.